WACANA VISUAL ILUSTRASI KORUPSI DALAM RUBRIK OPINI KOMPAS PERIODE 2011 - Noval Talani Sufriyanto (FBS UNY, 2012)
Illustration is a visual language which is used by mass media for commenting news or hot issues which develop in society. Editorial illustration, for example, not only plays a role as an esthetic element at the rubric but also can describe its attitude and the media politic line in which it was published. During 2011 period, Kompas has been lightened up many corruption cases that still happen this day, not only through editorial illustration but also through an opinion article illustration. Both of those illustrations put out the opinion rubric in Monday-Saturday edition. This paper discusses the illustration meaning and its relation within the article, the ways in which the corruption’s information was shown through illustration and the publics’ interpretation to the corruption’s illustration which was put on the opinion rubric at Kompas during 2011 period. To discover the answer of the problems that are investigated and to obtain the purpose which has been settled, this research uses qualitative approach with discourse analysis method. Through this research, a process model of visual discourse construction is also found.